Acute Kidney Injury in Adult Patients With Hepatocellular Carcinoma After TACE or Hepatectomy Treatment - Mou, Zhixiang; Guan, Tianjun; Chen, Lan (Frontiers in Oncology, 2022)
Background: Acute kidney injury (AKI) is one of the most common complications in patients with cancer, yet the specific reasons, mechanisms and influences of AKI are not clear in hepatocellular carcinoma (HCC) after treatment. This meta-analysis aimed to find out the risk factors and the impact on mortality of AKI in adult patients with HCC after treatment using the available published data. Methods: We performed a systemic literature search using PubMed, Web of Science, and Embase, encompassing publications up until Nov 30, 2021 (inclusive), 17 cohort studies involving 11,865 patients which fulfilled the pre-specified criteria were included for the meta-analysis. The number of AKI/non-AKI patients identified by risk factors, the number of death patients related AKI/non-AKI, the incidence rates, the mortality rates, and the irreversible rates of AKI were derived and analyzed by STATA. Results: Age, diabetes mellitus (DM) and the number of TACE sessions are risk factors of AKI in HCC patients after TACE; male, age, DM, major resection of the liver and operation related transfusion are risk factors of AKI in HCC patients after hepatectomy. The risk of mortality with renal failure due to AKI is up to 4.74 times higher than those without AKI in a short term observation period after TACE treatment. Conclusions: HCC patients with DM should be paid attention to the risk of AKI; the occurrence of AKI during TACE treatment is very dangerous and should be considered a strong red flag, which obviously with regards to extremely high risk of death in a short period. Furthermore studies are needed to detect more AKI associations in HCC patients.